Trismus Analysis Due to Head Trauma in Forensic Cases: Case Report - Langit, Ken Sekar; Kaurow, Farah Primadani; Yuniastuti, Mindya; Aeurkari, Elza Ibrahim (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Head trauma frequently happens in cases of physical violence, particularly in cases of abuse. A common sign of head trauma is trismus, characterized by difficulties in mouth opening, which can diminish an individual's quality of life and disrupt daily activities. The prognosis of trismus is contingent upon various factors, necessitating appropriate management in its therapy. The age factor and the severity of the etiology of trismus must be evaluated to determine the appropriate treatment. This condition also influences the decision-making over the classification of the wound documented in the Visum et Repertum for judicial purposes.